Nutrient recovery and crop yield enhancement in irrigation with reclaimed wastewater: a case study. Issue 3 (16th March 2017) - Vergine, Pompilio; Lonigro, Antonio; Salerno, Carlo; Rubino, Pietro; Berardi, Giovanni; Pollice, Alfieri
Abstract: The paper reports results of treated wastewater reuse field experiments carried out in Apulia (Southern Italy). Fennel and lettuce were irrigated with four different water sources: three reclaimed wastewater streams, obtained by applying different treatment schemes to the same municipal wastewater, and a conventional source (well water). Differences between the three effluents were significant in terms of suspended solids and faecal indicators. Both lettuce and fennel yields were enhanced by the high content of nutrients in the effluent of one of the treatment plants, which had been operated for partial nitrogen removal. In particular, fennel productivity was enhanced by replacing chemical fertirrigation with the supply of nutrients contained in the irrigation water.